ANALISIS PENGARUH HARGA, PROMOSI DAN SALURAN DISTRIBUSI TERHADAP PENINGKATAN VOLUME PENJUALAN YOGHURT PADA PT. SENTRA AGRI MULIA LESTARI SEMARANG - Samto; Intan Imam Sutanto (E-logis : Jurnal Ekonomi Logistik, 2021)
Tight business competition requires each company to compete with each other, so that price fixing, promotion, and distribution channels that are effective and efficient in exploiting their resources must be done to increase sales volume. The purpose of this study was to determine the effect of price, promotion, and distribution channels on increasing the sales volume of yogurt at PT. Sentra Agri Mulia Lestari Semarang. This study took a sample of 109 respondents with a purposive sampling technique. The population in this study were yogurt consumers from PT.Sentra Agri Mulia Lestari Semarang with the age requirement from 18 years to 40 years with. The data was collected using questionnaires, interviews and literature review. The data analysis technique used is the simultaneous significant test (F test) using Statistical Product and Service Solution (SPSS) v. 25. By determining the variable Price (X1), Promotion (X2), Distribution Channels (X3), and Sales Volume (Y). The results of this study can be seen from the results of the simultaneous significant test of the F test with a value of Fcount of 40.100 while Ftable is 2.69. This shows that the value of Fcount> Ftable 40,100> 2.69 with a significance value of 0,000